Kirsten and the new girl - Shaw, Janet Beeler, 1937- (The American girls collection, 2000)
When a new girl arrives at school, Kirsten is jealous, completely forgetting how scared and lonely she felt the year before when she was the new girl in school. Gives instructions for making a friendship pillow like those made in the 1850s.